Release and adoption of improved potato varieties in Southeast and South Asia - Gatto, M.; Hareau, Guy; Pradel, W.; Suarez, V.; Qin, J. (International Potato Center, 2018)
In this study, we close the identified gaps in the existing literature and databases by documenting release and adoption of improved potato varieties in seven major potato producing countries in Southeast, South, and East Asia. Methodologically, this study adopts a refined expert elicitation (EE) approach applied in previous projects. EE workshops were used as an inexpensive alternative to the collection of national representative adoption data. An average of 15 experts working in the potato value chain participated in a one-day event to elicit perceived adoption rates and to update release databases. In total, 347 experts attended 23 workshops which were held during 2014-2016.